Parental Ethnotheories about Learning and Cognitive Development during Early Childhood among the Bayangi Tribe in Cameroon - Takang, Kelly Tabe; Besong, Magdalene Ayuk (International Journal on Integrated Education, 2021)
Although a plausible link between parental ethnotheories and cognitive development have been suggested, studies addressing specifically parental ethnotheories about learning and early cognitive development in Sub-Saharan African is limited. This study aimed to investigate a direct relationship between parents’ cultural ideas about learning and children’s cognitive development. A mixed-method design (Case study and Correlational) was used for the study. Participants included 222 parents of children aged five to six years old selected using the purposive sampling technique. Questionnaires and interviews were used for data collection. Parental ethnotheories about learning was associated with individual cognitive development (p=0.00) but not associated with social cognition or cognition in service of social ends (p=0.169). Therefore, parental ethnotheories about learning may influence cognitive competence in intellectual tasks such as in school or an educational setting, but has no significant influence on social competence emphasizing social responsibilities and relatedness to the family and peers.